GENETIC DIVERSITY OF TILLETIA SPP. CAUSES OF COVERED SMUT DISEASE OF WHEAT AND IT RESISTANCES - Th. A Farhan; J. M. Abed; A. A. Khadum; R. G. Al-ani (مجلة الأنبار للعلوم الزراعية)
The research was conducted in the Department of Plant Protection- College of Agriculture- Anbar University. Aimed to detected genetic diversity of fungal species responsible for covered smut disease in wheat and evaluate the effectiveness of inducers hydrogen peroxide, melatonin, and salicylic acid combating the disease and improving growth parameters. The genetic analysis revealed that the isolates R14 (Anbar - Al Jazeera) and O21 (Nineveh - Mosul) were closely related to the isolate identified as MH855829.1, showing a 99% identity with T. caries fungal isolates. Similarly, the isolates R5 (Salah al-Din - Makishifa) and R16 (Anbar - Al-Karma) similarity to the isolate MH114992.1, with a 99% match to T. controversa. Furthermore, the isolates R3 (Baghdad - Al-Ridwaniyah) and S21 (Salah al-Din - Samarra) were closely related to the isolate MH4980301.1, with a 99% match to T. indica. The results showed that the Nazar variety, without of pathogen, exhibited the highest absorption rate of 60%, outperforming all other varieties. Additionally, the Pora variety achieved the highest wet gluten percentage, reaching 45.50%. Using inducers (hydrogen peroxide, melatonin, and salicylic acid) at concentrations of 300, 400, and 500 ppm significantly reduced the infection of covered smut disease. The infection rate for hydrogen peroxide treatment was 15.93%, with the 500 ppm concentration being the most effective, reducing the infection rate to 17.96%. The best interaction was observed between hydrogen peroxide and the 500 ppm concentration, resulting in an infection rate of just 13.50%